The Urgency of Narcotics Law Certainty in Indonesia After the Ratification of the Single Convention for Medical Purposes - Aringga, Rino Dedi; Saputra, Agung Arafat (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2023)
Judicial Review of Law Number 35 of 2009 concerning Narcotics in Indonesia is currently a step to reform the law on the use of narcotics, one of which is marijuana, so that it can be used for medical purposes. Not a few, patients with diseases who need alternative treatment using marijuana extracts must be hindered by regulations that bind Law Number 35 of 2009 concerning Narcotics. Indonesia adopted the results of The United Nation's Single Convention On Narcotic Drugs 1961 or (single convention) as a step to combat illicit trafficking and misuse of narcotics which was made into narcotics law in Indonesia which is contained in Law Number 35 of 2009 today. The purpose of this writing and research is so that the government and society can increase their concern for the rights of citizens in carrying out the constitutional mandate. As stated in Article 28 H of the 1945 Constitution,